Model Kebijakan Pendidikan Karakter di Madrasah - Supa’at (Jurnal Pendidikan Islam, 2014)
The behavior deviationism in almost of our daily activities has caused realization that “character education” is very important, and the fact that our education system failed to achieve its goals. Therefore, it looks asif there were no solutions – multidemention crisis. Education must be a solution of a nation to gain the true development and prosperity. To know what realy happen ini our educational system and practice, it was done a research, in the 29 Islamic Senior High Schools (MA) in Kudus. This reseacrh findings show that, the concept of character education has substantively the same concept with the system of Islamic school education (madrasah), its difference is only in the referable value. The concept of philosophocal character education refers to antropocentic, and madrasah refers to theocentris (religion). The socio-historic system of madrasah is realy the model of character education or character based on character that is suitable with the condition in Indonesia.